2010
DOI: 10.1038/jid.2009.209
|View full text |Cite
|
Sign up to set email alerts
|

MAPKAPK-2 Signaling Is Critical for Cutaneous Wound Healing

Abstract: Cutaneous wound healing is a complex process, which is heavily dependent on successful inflammatory action. Mitogen-activated protein kinase (MAPK)-activated protein kinase-2 (MAPKAPK-2 or MK2), a major substrate of p38 MAPK, has been shown to be a major player in multiple inflammatory diseases, but its role in cutaneous wound healing has not yet been explored. In this study, by comparing excisional wounds made on the backs of MK2 knockout (KO) and MK2 wild-type (WT) mice, we found that the kinetics of wound h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Additional studies indicate that p38␣ is the predominant isoform involved in cytokine production in vivo following lipopolysaccharide (LPS) stimulation (43), and gene transfer of p38␣ and the upstream activator MKK3 significantly increased expression of bFGF and PDGF-A in the normal heart (45), further supporting the concept of independent, non-redundant functions of p38 MAPK isoforms. In addition to p38␣, knockdown of the p38 MAPK pathway protein MK2 or HSP27 in stromal cells also reduced cord formation along with VEGF, bFGF, and IL-6 secretion, a result substantiated in MK2 knockout mice, where reduced angiogenesis in wound healing is in concert with reduced expression of several cytokines (GM-CSF, VEGF, IFN␥, MCP1, TNF, IL-6, and IL-1␤) compared with wild-type mice (46). In addition, targeted deletion of MK2 in macrophages led to decreased production of LPS-induced tumor necrosis factor (TNF), IL-6, and other cytokines (47).…”
Section: Discussionmentioning
confidence: 76%
“…Additional studies indicate that p38␣ is the predominant isoform involved in cytokine production in vivo following lipopolysaccharide (LPS) stimulation (43), and gene transfer of p38␣ and the upstream activator MKK3 significantly increased expression of bFGF and PDGF-A in the normal heart (45), further supporting the concept of independent, non-redundant functions of p38 MAPK isoforms. In addition to p38␣, knockdown of the p38 MAPK pathway protein MK2 or HSP27 in stromal cells also reduced cord formation along with VEGF, bFGF, and IL-6 secretion, a result substantiated in MK2 knockout mice, where reduced angiogenesis in wound healing is in concert with reduced expression of several cytokines (GM-CSF, VEGF, IFN␥, MCP1, TNF, IL-6, and IL-1␤) compared with wild-type mice (46). In addition, targeted deletion of MK2 in macrophages led to decreased production of LPS-induced tumor necrosis factor (TNF), IL-6, and other cytokines (47).…”
Section: Discussionmentioning
confidence: 76%
“…MK2 activation is also required for cytokine production during inflammatory responses [129]. It was recently demonstrated that MK2 activity is essential to cutaneous wound healing [130] and thus an enzyme of this group may be a modulator of tissue injury/immune response in AM epithelia.…”
Section: Resultsmentioning
confidence: 99%
“…Prevention of recruitment and activation of natural killer T cell (NKT) to the wound bed leads to enhanced wound healing [66]. Mitogen-activated protein kinase-activated protein kinase 2 (MAPKAPK-2 or MK2) gene expression in macrophages is critical in wound healing based upon studies from MK2 knockout mice [67]. …”
Section: Chemokines In Healthmentioning
confidence: 99%